The impact of manufacturing parameters on corrosion resistance of additively manufactured AlSi10Mg-samples: A design of experiments approach. (October 2022) - Maurer, Oliver; Herter, Franziska; Bähre, Dirk
Abstract: Metal-additive manufacturing provides opportunities to design products more freely and complex than conventional machining. Highly functional parts can be produced. Besides geometry, each part must meet large varieties of requirements. AM-Aluminum is known to form a protective passive layer in many cases of corrosion attack, which inhibits further damage. Corrosion damage is an issue if electrolyte relics remain on the surface if Electrochemical Machining is used for post-processing. In this study corrosion morphology and corrosion loss are evaluated and matched to settings of the Laser Powder-Bed Fusion machine. Design of Experiments was applied and extended by introducing normalized effects.